USING TWO STEP CLUSTER ANALYSIS TO IDENTIFY PARTNERSHIP ACTIVITIES OF MICRO AND SMALL INDUSTRY (MSI) IN INDONESIA - Setyaningrum, Idfi; Sari, Dyah Wulan; Handoyo, Rossanto Dwi (The journal of contemporary issues in business and government, 2021)
In economic development in Indonesia, the micro and small industry (MSI) has an important role. The phenomena reflect the ability of the MSI to withstand the economic crisis that Indonesia has experienced. One of the efforts to develop MSI is through a partnership strategy. The partnership in question is mutually beneficial business cooperation between MSI and a larger industry so that it needs, benefits, and strengthens. However, in MSI businesses, the number of businesses that have formed partnerships is still relatively small. The number of MSI businesses that carry out partnership activities is only 8.28%. It means that the partnership activities between Large Industry and MSI, mandated in the Act, have not entirely run as expected. This study aims to map and analyze the characteristics of the MSI partnership pattern in Indonesia based on the economic corridors and partnership activities using the two-step cluster method approach. The data used were the data from the MSI annual survey in all provinces in Indonesia conducted by the Central Statistics Agency in 2019 with a sample of 90,295 industries. The research found that the distribution of three clusters regionally as follows: Cluster 1 consists of the Sumatra Corridor (14.7%) and the Java Corridor (17.7%), Cluster 2 consists of the Sumatra Corridor (5.9%), the Bali - Nusa Tenggara Corridor (8.8%) ), and the Maluku-Papua Corridor (11.8%), Cluster 3 consists of the Sumatra Corridor (8.8%), the Sulawesi Corridor (17.7%), and the Kalimantan Corridor (14.7%) of all provinces in Indonesia with the characteristics of a partnership pattern as follows Cluster 1 patterns of operational cooperation between MSI and Large Industries on the fulfillment of raw materials and technology transfer with a focus on improving the quality of raw materials, cluster 2 of the Core Plasma pattern, Sub Contracts, Profit Sharing, Joint Ventures focused on solving capital problems, and cluster 3 of general trading patterns that focused on product marketing as well as increasing partnerships to guarantee the absorption of products.